Peculiar features of electron spin resonance spectra in (Ca,Na)-doped lanthanum manganites - Tovstolytkin, A.I.; Pogorily, A.M.; Podyalovskii, D.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The analysis of the ESR spectra for the powdered samples of (Ca,Na)-doped manganites have been performed in the temperature range 220–320 K. It is shown that the samples under investigation are characterized by a broadened para- to ferromagnetic transition and complicated spectra within the transitional region. The conclusion is made that the satisfactory interpretation of the resonance data is only possible if the interference of the coexisting phases is taken into account within the transitional region. Under these conditions, the resonance field for the paramagnetic phase is shown to increase with the temperature lowering, while that for the ferromagnetic phase first decreases and then approaches a value characteristic of the uniformlymagnetized ferromagnetic sample. It is noted that the results obtained are in compliance with those predicted theoretically for the spherical particles containing a mixture of the paramagnetic and ferromagnetic phases.